2020
DOI: 10.1111/jocn.15286
|View full text |Cite
|
Sign up to set email alerts
|

A structural equation model of health‐related quality of life among Thai men with chronic obstructive pulmonary disease

Abstract: Aim and objectives To identify physiological, psychological and socioenvironmental factors that affect the health‐related quality of life of Thai men living with chronic obstructive pulmonary disease. The vast majority of Thai persons living with chronic obstructive pulmonary disease are men. Background Little is known about the health‐related quality of life of Thai people living with chronic obstructive pulmonary disease or about the physiological and psychosocial factors that most affect it. Applying a prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…COPD is a respiratory disease characterized by pathologic changes in the respiratory system. Clinically, it includes localized obstructive emphysema and diffuse obstructive emphysema [ 15 ]. The main pathologic changes are increased residual volume and sustained expansion of pulmonary tissue on terminal bronchioles along with the destruction of the alveolar septum and reduced elasticity of pulmonary tissue, leading to increased volume [ 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…COPD is a respiratory disease characterized by pathologic changes in the respiratory system. Clinically, it includes localized obstructive emphysema and diffuse obstructive emphysema [ 15 ]. The main pathologic changes are increased residual volume and sustained expansion of pulmonary tissue on terminal bronchioles along with the destruction of the alveolar septum and reduced elasticity of pulmonary tissue, leading to increased volume [ 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Five studies reported an association between general health perceptions and overall QOL. More positive general health perceptions were found to be associated with better overall QOL in patients having HIV/AIDS (Alsayed et al, 2017;Mohamed et al, 2017), ESRD (Jung & Kim, 2020), myocardial infarction (Kang et al, 2018), and COPD (Peepratoom et al, 2020).…”
Section: Associations Among Five Main Conceptsmentioning
confidence: 97%
“…The associations between symptoms and functional status, general health perceptions, and overall QOL were supported by 13, three, and seven studies, respectively. For instance, more severe symptoms were significantly associated with poorer physical functioning in patients with HIV/AIDS (Alsayed et al, 2017), Parkinson's disease (Chekani et al, 2016), ESRD (Jung & Kim, 2020), heart failure (Lawson et al, 2018), COPD (Peepratoom et al, 2020), and fibromyalgia (Rutledge et al, 2007); in healthy women (Savoy & Penckofer, 2015); and in the elderly (McKay et al, 2020;Spoelstra et al, 2010a;2010b;. Also, more severe symptoms were significantly associated with poorer general health perceptions in patients having HIV/AIDS (Alsayed et al, 2017) and heart failure (Lawson et al, 2018) as well as with lower overall QOL in patients having ESRD (Jung & Kim, 2020), heart disease (Kang et al, 2018;Wang et al, 2016), breast cancer (Oh & Cho, 2020), and COPD (Peepratoom et al, 2020) and in healthy women (Savoy & Penckofer, 2015).…”
Section: Associations Among Five Main Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 It has also been suggested that the level of social support is an important predictor of caregiver quality of life, and the higher the level of perceived social support, the higher the level of quality of life of the individual. 19 Caregivers who respond negatively when providing care to patients may create a vicious cycle effect with their poor mental health status. 20 Trait coping style is a relatively stable behavioral and cognitive approach taken by individuals in the face of various stressful events, and includes both positive and negative coping styles.…”
Section: Introductionmentioning
confidence: 99%